PENERAPAN NILAI-NILAI ISLAM DALAM SEBUAH SIMULASI PERANCANGAN HUNIAN RUMAH TINGGAL SEDERHANA - Ardhy, Surya (Universitas Aisyiyah Yogyakarta, 2018)
Abstract: This study aims to explore Islamic values that have implications on the habitation aspects and illustrate how these values can be translated in the physical embodiment of dwelling. Literature review has been done to find the formulation of Islamic principles in residential environment. Precedent study by observing housings close to hypothetical site of the design simulation case was also taken as a part of contextual design approach. The concepts referred in design derived from the formulation of principles and contexts. This study concludes that Islamic values are highly potential to be explored in developing residential design concepts. The principles derived from Islamic values are more universal-qualitative criterias, so that in the realm of design, can be implemented with a very adaptive to the local contexts.Keyword: dwelling, Islamic values, design simulation, context